Strategy for Establishing an Arabic Language Environment in the Palengaan Laok Village School, Palengaan Pamekasan - Hamdy, Mohammad Zainal; Bahar, Syaiful; Zainullah, Zainullah; Zubairi, Ach. (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Learning Arabic will be maximized and perfect by creating a conducive language environment. The language environment provides intensive teaching to students to practice their language skills both orally and in writing. Learning Arabic in the classroom generally prioritizes understanding of linguistic rules including nahwu and sharaf, communicative Arabic practice is rarely applied in class because learning refers to the curriculum and specified material. The language environment is a place for students to practice their language skills, especially speaking skills. Armed with an understanding of the language rules learned in class, students have a great opportunity to apply their Arabic language skills with linguistic activities that are implemented in a speaking environment to the fullest. The type of research used is descriptive qualitative research. The researcher chose this method because the data obtained by the researcher in the field was stated in verbal form and in descriptive analysis without using statistical data. This research was conducted with an inductive point of view, the researcher went into the field first to identify the problem under study. Then the researchers conducted further research and collected data related to the formation of a language environment. The language environment in schools and boarding schools in Palengaan Laok provides opportunities for students to be creative in practicing their language skills as well as various language activities that support the development of their language skills significantly, with a language environment. Arabic learning process becomes more dynamic, effective and varied.